VD_FINDINFO HC / 2014 / 235 vom 20. März 2014 - VD Tribunal cantonal (2014)
DÉPENS, FRAIS JUDICIAIRES, PROCÈS DEVENU SANS OBJET | 241 CPC (CH), 242 CPC (CH), 23 al. 1 TFJC (2010), 27 al. 1 TFJC (2010)